AKUNTABILITAS PENGELOLAAN ALOKASI DANA DESA (Studi Kasus Di Desa Long Bang Kecamatan Peso Hilir Kabupaten Bulungan) - Thomas Djaka Setya; Aysi Rinda Rosdiana; Mastotok Illah (STIE Kertanegara Malang, 2022)
This thesis research was conducted at the Long Bang Village Office, Peso Hilir District, Bulungan Regency. This study aims to analyze and find out how Accountability of Village Fund Allocation Management (ADD) is in Long Bang Village. This type of research is a qualitative approach description in order to know the planning, implementation, administration, and accountability in the Management of Village Fund Allocations in Long Bang Village, Peso Hilir District, Bulungan Regency. Sources of data used are primary data obtained from interviews and secondary data obtained from related documents. In addition, for data analysis using triangulation techniques. The focus of this research consists of planning, implementation, administration and accountability in the Village Fund Allocation Management (ADD) system in Long Bang Village. The results of this study indicate that the stages of planning, implementation, administration, and accountability have been carried out properly, as evidenced by the village party having made accountability starting from planning to implementing each activity. Keywords: Accountability, Village Fund Allocation (ADD)